2022
DOI: 10.3389/fsufs.2021.759638
|View full text |Cite
|
Sign up to set email alerts
|

Toward Agricultural Intersectionality? Farm Intergenerational Transfer at the Fringe. A Comparative Analysis of the Urban-Influenced Ontario's Greenbelt, Canada and Toulouse InterSCoT, France

Abstract: Peri-urban agriculture can foster the resilience of metropolitan areas through the provision of local food and other multifunctional agricultural amenities and externalities. However, in peri-urban areas, farming is characterized by strong social uncertainties, which slow the intergenerational transfer of farm operations. In this article, we tackle the beliefs that underlie farmers' decision-making to identify planning opportunities that may support farm intergenerational transfers. The design of an institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Above all, the existing literature has predominantly focused on the externalities of land transfer [84,85], poverty reduction mechanisms [86][87][88], and market mechanisms among farmers [89,90]. Wu et al conducted a study using data from 2011 to 2014 in rural China, which revealed that farmer participation in land transfer led to a significant reduction in fertilizer application intensity in a grain-growing region in Western China [91].…”
Section: Impact Of Land Transfer Behavior (Str) On Farmers' Livelihoo...mentioning
confidence: 99%
“…Above all, the existing literature has predominantly focused on the externalities of land transfer [84,85], poverty reduction mechanisms [86][87][88], and market mechanisms among farmers [89,90]. Wu et al conducted a study using data from 2011 to 2014 in rural China, which revealed that farmer participation in land transfer led to a significant reduction in fertilizer application intensity in a grain-growing region in Western China [91].…”
Section: Impact Of Land Transfer Behavior (Str) On Farmers' Livelihoo...mentioning
confidence: 99%